2002
DOI: 10.1109/tmag.2002.803177
|View full text |Cite
|
Sign up to set email alerts
|

Mossbauer investigation of Sr-Fe-O hexaferrites with La-Co addition

Abstract: M-type Sr 1 La Fe 12 Co O 19 ferrite powders with = 0 to 0.4 were investigated using Mössbauer spectrometry in the 77 K-550 K temperature range. The Mössbauer spectra were fitted by assuming that Co 2+ is present in both 4f 2 and 2a octahedral sites, and that some Fe 2+ is present in the 2a site. On increasing , the main changes concern the Mössbauer contributions of the 12k, 4f 2 and 2b sites. These changes are interpreted in relation with the Co 2+ -Fe 3+ substitution at the 4f 2 site, the Fe 3+ -Fe 2+ valen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
24
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 8 publications
10
24
1
4
Order By: Relevance
“…4). The spectra were fitted assuming a distribution of Co 2+ in 4f 2 (mainly) and 2a octahedral sites, in agreement with previous investigations [6][7][8]. As Co 2+ was introduced in lower proportion than La 3+ , a small amount of Fe 2+ is assumed to be present in the 2a site, to keep the electroneutrality, in agreement with the valence change of Fe 3+ to Fe 2+ that occurs at the 2a site in the LaFe 12 O 19 compound [13].…”
Section: Structural Analysessupporting
confidence: 75%
See 2 more Smart Citations
“…4). The spectra were fitted assuming a distribution of Co 2+ in 4f 2 (mainly) and 2a octahedral sites, in agreement with previous investigations [6][7][8]. As Co 2+ was introduced in lower proportion than La 3+ , a small amount of Fe 2+ is assumed to be present in the 2a site, to keep the electroneutrality, in agreement with the valence change of Fe 3+ to Fe 2+ that occurs at the 2a site in the LaFe 12 O 19 compound [13].…”
Section: Structural Analysessupporting
confidence: 75%
“…In agreement with the magnetic measurements, the presence of these magnetic impurities can be partly responsible for both the decrease of the coercive field and the decrease of the rectangularity for x > 0.2. The cationic distribution of Co 2+ in Sr 1−x La x Fe 12−x Co x O 19 hexagonal ferrites was recently investigated by Möss-bauer spectrometry, Raman spectroscopy, and nuclear magnetic resonance [5][6][7][8][9][10]. It was shown that most of the Co 2+ is substituted for Fe 3+ in the octahedral 4f 2 and 2a sites, in agreement with the magnetization measurements.…”
Section: Structural Analysesmentioning
confidence: 57%
See 1 more Smart Citation
“…Their magnetic properties are qualitatively interpreted based on micromagnetic models, but there is still some research interest [2][3][4][5][6][7], focused on the development of a cheaper manufacturing process that will not affect the enhanced magnetic properties of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…ossbauer spectrometry and nuclear magnetic resonance in Sr 1Àx La x Fe 12Àx Co x O 19 ferrites prepared by a conventional ceramic process [3][4][5]. It was shown that Co 2þ ions substitutes for Fe 3þ in both 4f 2 and 2a sites.…”
Section: Introductionmentioning
confidence: 99%